2012
DOI: 10.1159/000339829
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitivity Modulates the Growth Response during the First Year of High-Dose Growth Hormone Treatment in Short Prepubertal Children Born Small for Gestational Age

Abstract: Aim: To study the relationship between insulin sensitivity and growth response in short children born small for gestational age (SGA) treated with growth hormone (GH). Methods: Randomized, open-label, 24-month intervention study in 40 short prepubertal SGA children [age (mean ± SD) 5.3 ± 1.5 years], who either remained untreated (n = 20) or were treated with GH (66 µg/kg/day; n = 20). Changes in fasting glucose, insulin, quantitative insulin sensitivity check index (QUICKI), IGF-1 and leptin after 1 and 2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 76 publications
0
7
1
Order By: Relevance
“…It is therefore questionable if these temporary changes are relevant. Like others,[383940] we are also unable to detect a tendency to deterioration with a longer period of GH treatment. However, puberty might have an influence, as a relatively large number of abnormal values were found in the individual last prepubertal year of these children.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…It is therefore questionable if these temporary changes are relevant. Like others,[383940] we are also unable to detect a tendency to deterioration with a longer period of GH treatment. However, puberty might have an influence, as a relatively large number of abnormal values were found in the individual last prepubertal year of these children.…”
Section: Discussioncontrasting
confidence: 61%
“…In line with the findings in all other studies,[69172337] in our group none of the children developed diabetes. The significant rise of insulin levels in oGTT has also been reported before, but the results differ in detail: some studies find changes in insulin levels only after 6 months[38] or the first year,[3940] others see a continuous rise throughout their follow-up period. [6841] In our cohort of prepubertal children, apart from fasting values, we could demonstrate a stabilization of insulin levels after the first year of treatment.…”
Section: Discussionmentioning
confidence: 75%
“…We and others have reported that the growth response to GH therapy in short SGA children is associated with baseline insulin sensitivity and IGF-1 levels (2,3). Children with the highest baseline IGF-1 levels had lower insulin sensitivity, lower height velocity, and lower IGF-1 responses after 1 year of GH therapy (3).…”
mentioning
confidence: 74%
“…Insulin sensitivity (IS) at baseline has been associated with baseline IGF-I levels, and may predict growth response [16,17]. These findings suggest that variations in baseline IGF-I levels may be related to both growth and metabolic response to GH treatment.…”
Section: Introductionmentioning
confidence: 99%